2016
DOI: 10.1088/1758-5090/8/4/045005
|View full text |Cite
|
Sign up to set email alerts
|

3D bioprinted glioma stem cells for brain tumor model and applications of drug susceptibility

Abstract: Glioma is still difficult to treat because of its high malignancy, high recurrence rate, and high resistance to anticancer drugs. An alternative method for research of gliomagenesis and drug resistance is to use in vitro tumor model that closely mimics the in vivo tumor microenvironment. In this study, we established a 3D bioprinted glioma stem cell model, using modified porous gelatin/alginate/fibrinogen hydrogel that mimics the extracellular matrix. Glioma stem cells achieved a survival rate of 86.92%, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
208
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 267 publications
(215 citation statements)
references
References 53 publications
6
208
0
1
Order By: Relevance
“…Encapsulated NSCs had an initial cell viability of ~75% and were able to differentiate into neurons and glial cells. Similar results were found with a bioink of sodium alginate, fibrinogen, and gelatin (Dai et al, 2016). The bioink was soaked in calcium chloride and thrombin solutions after printing to crosslink the sodium alginate and fibrinogen components, respectively.…”
Section: Strategies For Biomaterials Printingsupporting
confidence: 73%
“…Encapsulated NSCs had an initial cell viability of ~75% and were able to differentiate into neurons and glial cells. Similar results were found with a bioink of sodium alginate, fibrinogen, and gelatin (Dai et al, 2016). The bioink was soaked in calcium chloride and thrombin solutions after printing to crosslink the sodium alginate and fibrinogen components, respectively.…”
Section: Strategies For Biomaterials Printingsupporting
confidence: 73%
“…bioprinted Hela cells with gelatin/alginate/fibrinogen hydrogel and found that MMP-2 and MMP-9 expression of tumor cells in hydrogel were higher than those of the 2D control 16 . Previously, we have bioprinted a brain tumor model by extruding glioma stem cells-laden hydrogel 17 . But it is known that solid tumor contains not only tumor cells but also a variety of stromal cells, which are the important sources of extracellular matrix and cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…High-throughput pharmacological study [36,78] 3D bioprinting Primary feline H1 cardiomyocytes First rhythmic beating of 3D printed structure [93][94][95] Lung Microfabrication Epithelial cells Use of porous membrane to mimic lung functions [31,37] 3D bioprinting A549 cells and EA hy926 cells World's first 3D bioprinted lung tissue [101] Bone 3D bioprinting BMSCs High viability in microextrusion-based bioprinting [108,109,158,159] Cancer Self-assembled Intestinal stem cells Discovery of LGR5+ intestinal stem cells [52,62] Microfabrication Breast cancer cells Perfusable human microvascularized bone-mimicking (BMi) microenvironment [81,168] 3D bioprinting OVCAR-5 and MRC-5 cells Insight into complex cell-cell communication in 3D [113][114][115][116][117] Multi Self-assembled Liver, gut, vessel cells High throughput hanging drop [30,[49][50][51][52] Microfabrication Liver, heart, and vessel cells Automated control of perfusion [11,19,27,32] 3D bioprinting NPC and HCT-116 cells Multiorgan bioprinted model [30,122] a)…”
Section: Engineering Technologiesmentioning
confidence: 99%
“…[116] In summary, 3D bioprinted glioma model provides a novel alternative tool for studying glioma genesis, glioma stem cell biology, drug resistance, and glioma anticancer drug susceptibility in vitro. [115] Other groups have generated different cancer 3D in vitro models including models for bone and breast cancers using 3D bioprinting. [116,117] …”
Section: Bioprinted Cancer Modelsmentioning
confidence: 99%